PENERAPAN HERMENEUTIK DHEMITOLOGI RUDOLF BULTMANN PADA RANAH PENDIDIKAN AGAMA ISLAM - Saefullah, Muhammad; Lailiyah, Siti; Imron, Ali (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
This research discusses Bultmann's theological hermeneutics, namely Dhemitology, a philosophical theory that examines issues in the Holy Scriptures which are sacred in the form of myths and are still a mystery to be proven by exploring their original and hidden meanings. This theory aims to interpret the ideas, motifs and stories in revelation so that they become clear and transparent and still remain within the limits of an approach that focuses on the objectification of language. This research uses the library research method (library study). In the form of a series of activities related to data collection methods from library books. The resulting analysis is that the order of worship in Islam is not just a mere Shari'a, but after a thorough study of its meaning, it is found that there are many benefits contained in it, as well as scientific rationale.